Datacenter in a box: test your SDN cloud-datacenter controller at home - Teixeira, José (2013)
In the last years, the widespread of Cloud computing as the main paradigm to deliver a large plethora of virtualized services significantly increased the complexity of Datacenters management and raised new performance issues for the intra-Datacenter network. Providing heterogeneous services and satisfying users’ experience is really challenging for Cloud service providers, since system (IT resources) and network administration functions are definitely separated. As the Software Defined Networking (SDN) approach seems to be a promising way to address innovation in Datacenters, the paper presents a new framework that allows to develop and test new OpenFlow–based controllers for Cloud Datacenters. More specifically, our framework enhances both Mininet (a well–known SDN emulator) and POX (a network controller written in python), with all the extensions necessary to experiment novel control and management strategies of IT and network resources.